Comparative Structural Analysis of 3D-Printed PLA and ABS for Flexible Quadcopter Airframe Extensions - Widyanto, Dwi; Lengari, Andre B Sjukur; Hermawan, Aldi Henda; Wicaksono, Dhimas; Setiawan, Ferry (Universitas Muhammadiyah Yogyakarta, 2026)
This study evaluates the structural performance of a 3D-printed Quadcopter Airframe Extension, focusing on optimizing payload capacity and flight efficiency through cost-effective additive manufacturing. To ensure computational efficiency for macro-scale assessment, the finite element analysis (FEA) model treats the 3D-printed filaments as homogeneous solid bodies with isotropic elastic properties. The simulation setup applies a fixed boundary condition at the four motor mounts to simulate thrust reaction points, while incremental vertical payloads from 1 kg to 16 kg are distributed evenly across the landing gear skids. The analysis measured von Mises stress distribution and Safety Factor (SF) to ensure reliability against potential dynamic flight maneuvers, applying a minimum safety factor of 3. While both materials remained within their elastic regions, PLA demonstrated superior mechanical properties. PLA maintained a safety factor of 3.11 at a maximum 16 kg load, whereas ABS reached a comparable safety factor (3.24) only up to an 11 kg load. The results indicate that PLA's higher stiffness and superior interlayer adhesion provide better dimensional stability and lower deformation. Consequently, PLA is more suitable for flexible drone extensions, offering a greater safety margin under equivalent static loading constraints. Ultimately, this research validates homogeneous macro-scale FEA as an essential engineering tool for reducing prototype risks and development costs in UAV design.